Transcending capitalism growth strategies for biodiversity conservation. Issue 2 (3rd November 2021) - Moranta, Joan; Torres, Cati; Murray, Ivan; Hidalgo, Manuel; Hinz, Hilmar; Gouraguine, Adam
Abstract: The unlimited economic growth that fuels capitalism's metabolism has profoundly transformed a large portion of Earth. The resulting environmental destruction has led to an unprecedented rate of biodiversity loss. Following large‐scale losses of habitats and species, it was recognized that biodiversity is crucial to maintaining functional ecosystems. We sought to continue the debate on the contradictions between economic growth and biodiversity in the conservation science literature and thus invite scholars to engage in reversing the biodiversity crisis through acknowledging the impacts of economic growth. In the 1970s, a global agenda was set to develop different milestones related to sustainable development, including green–blue economic growth, which despite not specifically addressing biodiversity reinforced the idea that economic development based on profit is compatible with the planet's ecology. Only after biodiversity loss captured the attention of environmental sciences researchers in the early 2000s was a global biodiversity agenda implemented. The agenda highlights biodiversity conservation as a major international challenge and recognizes that the main drivers of biodiversity loss derive from economic activities. The post‐2000 biodiversity agendas, including the 2030 Agenda for Sustainable Development and the post‐2020 Convention on Biological Diversity Global Strategy Framework, do not consider the negative impacts of growth‐oriented strategies on biodiversity. As a result, global biodiversity conservation priorities are governed by the economic value of biodiversity and its assumed contribution to people's welfare. A large body of empirical evidence shows that unlimited economic growth is the main driver of biodiversity loss in the Anthropocene; thus, we strongly argue for sustainable degrowth and a fundamental shift in societal values. An equitable downscaling of the physical economy can improve ecological conditions, thus reducing biodiversity loss and consequently enhancing human well‐being. Abstract : Article impact statement : Moving away from growth‐based socioeconomic metabolism of capitalism is required and essential for successful biodiversity conservation. Abstract : Trascendiendo las Estrategias de Crecimiento Capitalista para la Conservación de la Biodiversidad Resumen: El crecimiento económico ilimitado que alimenta el metabolismo del capitalismo ha transformado profundamente una gran parte del planeta Tierra. La destrucción ambiental resultante ha traído como consecuencia una tasa sin precedentes de pérdida de diversidad biológica. Después de la pérdida a gran escala de hábitats y especies, se reconoció que la biodiversidad es crucial para mantener el funcionamiento de los ecosistemas. En este articulo buscamos seguir con el debate sobre las contradicciones entre el crecimiento económico y la biodiversidad en la literatura de las ciencias de la conservación y así invitar a los académicos a participar en la reducción de la crisis de biodiversidad dando a conocer los impactos del crecimiento económico. En la década de 1970, se estableció una agenda global para desarrollar diferentes metas relacionadas con el desarrollo sustentable, incluyendo el crecimiento económico verde y azul, la cual a pesar de no mencionar específicamente la biodiversidad reforzó la idea de que el desarrollo económico basado en ganancias es compatible con la ecología del planeta. Fue solamente después de que la pérdida de biodiversidad captó la atención de los investigadores de las ciencias ambientales a principios de la década de los 2000 que se implementó una agenda para la diversidad biológica. La agenda resalta que la conservación de la biodiversidad es un gran reto internacional y reconoce que las pincipales causas de la pérdida de la diversidad biológica derivan de las actividades económicas. Las agendas para la biodiversidad creadas después del 2000, incluyendo la Agenda 2030 para el Desarrollo Sustentable y el Marco de Trabajo de la Estrategia Mundial de la Convención sobre la Diversidad Biológica posterior a 2020, no consideran los impactos negativos de las estrategias para la biodiversidad orientadas por el crecimiento. Como resultado, las prioridades de la conservación mundial de la biodiversidad están gobernadas por el valor económico de la biodiversidad y la supuesta contribución que tiene para el bienestar de las personas. Una gran cantidad de evidencia empírica muestra que el crecimiento económico ilimitado es el principal conductor de la pérdida de diversidad biológica en el Antropoceno; por lo tanto, abogamos fuertemente por un decrecimiento sustentable y un cambio fundamental en los valores sociales. Una reducción equitativa de la economía física puede mejorar las condiciones ecológicas, reduciendo así la pérdida de biodiversidad y mejorando como consecuencia el bienestar humano.